Amination magnetic microsphere-carbon-based-layered double hydroxide composite material and preparation method and application thereof
By forming regular morphological magnetic microspheres on the surface of the carbon-based material and combining them with the LDH precursor, the problems of unevenness and stability of the existing carbon-LDH composite materials are solved, and the effect of efficient adsorption and removal of heavy metals is achieved.
Patent Information
- Application Number
- CN202310323489.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-29
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-03-29
AI Technical Summary
The existing carbon-LDH composite materials have defects such as unevenness, easy agglomeration, and poor stability, making it difficult to achieve excellent adsorption performance and long life.
The soft template method is used to directly form a regular morphological magnetic microsphere on the surface of the carbon-based material, and hydrothermal reaction is carried out under alkaline conditions by combining the LDH precursor to form an aminated magnetic microsphere-carbon-layered double hydroxide composite material.
It improves the specific surface area, adsorption sites and structural stability of the composite material, enhances the adsorption and removal capabilities of heavy metals, and has a simple process, convenient operation and low cost.
Smart Images

Figure CN116272918B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of remediation of environmental pollution by functional nanomaterials, relates to a heavy metal adsorption material, and specifically relates to an aminated magnetic microsphere-carbon-based-layered double hydroxide composite material, and a preparation method and application thereof. Background Art
[0002] Carbon-based materials are environmentally friendly, low-cost, high specific surface area, large porosity, and easy to modify. They are widely used in energy, separation and purification, electrode materials, sensors, and environmental pollution remediation. In the field of environmental remediation, the most commonly used carbon-based materials are carbon nanotubes (CNTs), biochar (BC), activated carbon (AC), carbon cloth, graphene oxide (GO), etc. These carbon materials have been used in the environmental field to remove heavy metal pollution in wastewater and sediments. However, the properties of carbon-based materials themselves are not suitable for all applications, such as poor water solubility, easy agglomeration, and difficult recycling. By adopting chemical regulation, introduction of heteroatoms, multi-material hybridization and other regulatory optimization methods, the key properties of carbon materials such as size, skeleton structure, microporous structure, and surface properties can be modified to make them have more excellent performance, so that they can be used in various fields. For example, the introduction of metal nanoparticles can increase the specific surface area of composite carbon-based materials, increase mass transfer rate, provide rapid electron transfer, and enhance the adsorption, degradation and conversion performance of carbon-based-nanomaterials on environmental pollutants. In addition, the combination of carbon-based materials and magnetic nanoparticles is a common method to enhance the remediation and separation performance of carbon-based materials for heavy metals. 2+ , Fe 3+ ) is mostly introduced by adding Fe during the preparation process. 2+ or Fe 3+ , condensed into Fe3O4 magnetic particles during the solvent volatilization process, distributed in the pores or surface of the carbon material. However, the magnetic particles in this method do not have a consistent nanostructure and controllable morphology, and the magnetic particles may block or destroy the pore structure of the carbon material, which may reduce the number and stability of functional groups on the surface of the composite material, thereby affecting the adsorption and stabilization effect of the carbon composite material on heavy metals. Therefore, how to regulate the nanostructure of magnetic particles, prepare magnetic microspheres with regular morphology, and ensure the effective load of magnetic microspheres on carbon materials is very important and necessary for improving the surface properties of carbon materials and obtaining an enhanced carbon-based composite material with a large specific surface area, multiple adsorption sites, and stable structure.
[0003] Layered double hydroxides (LDH) are ionic layered composite materials with a large surface area and abundant layered structure, excellent ion exchange performance, chemical stability, modification possibility, and controllable size and composition. They are low-cost and environmentally friendly, so they have great potential in the treatment of heavy metals in wastewater and sediments. However, the lack of functional groups and structural composition limits the ability of single LDH to repair environmental heavy metals. Based on this, researchers have proposed a strategy to combine LDH with carbon-based materials, by compounding LDH with carbon-based materials, introducing functional groups and improving the morphology and structure of carbon-based materials to improve the repair efficiency of pollutants. However, in the existing conventional carbon-based LDH composite materials, LDH and carbon-based materials are mainly prepared by physical mixing, and the stability of the composite materials obtained is still poor, which is not conducive to improving the adsorption performance and service life of the composite materials. In addition, the existing preparation methods of carbon-based-LDH composite materials are usually two-step synthesis methods, such as synthesizing LDH first and then mixing it with the carbon-based material dispersion, or directly drying the prepared carbon-based material to re-disperse the in-situ loading of LDH. These methods still have defects such as uneven redispersion of materials, insufficient uniformity of the synthesized composite materials, and unstable bonding. Therefore, obtaining a carbon-based-LDH composite material with excellent adsorption performance, good stability, easy separation, and environmental friendliness, as well as a matching preparation method with simple process, convenient operation, and low cost, is of great practical significance for promoting the promotion and application of carbon-based-LDH composite materials. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide an aminated magnetic microsphere-carbon-based-layered double hydroxide composite material having excellent adsorption performance, good stability, easy separation and environmental friendliness, as well as a preparation method and application thereof.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0006] A method for preparing an aminated magnetic microsphere-carbon-based layered double hydroxide composite material comprises the following steps:
[0007] S1. Mix the carbon-based material, iron salt, polyvinyl pyrrolidone, sodium acetate, amination agent and solvent, and stir to obtain a mixed solution A;
[0008] S2, subjecting the mixed solution A to a hydrothermal reaction to obtain an aminated magnetic microsphere-carbon-based composite material;
[0009] S3, mixing the aminated magnetic microsphere-carbon-based composite material, LDH precursor, urea and water, stirring to obtain a mixed solution B; the LDH precursor is a soluble divalent metal salt and / or a soluble trivalent metal salt for preparing layered double hydroxide;
[0010] S4. Performing a hydrothermal reaction on the mixed solution B to obtain an aminated magnetic microsphere-carbon-based-layered double hydroxide composite material.
[0011] The above preparation method is further improved. In step S1, the ratio of the carbon-based material to the iron salt is 100 mg to 500 mg: 0.002 mol to 0.01 mol; the ratio of the iron salt to the solvent is 3 mmol to 5 mmol: 30 mL to 100 mL; the ratio of the polyvinyl pyrrolidone, sodium acetate, amination agent and solvent is 2 g to 8 g: 2 g to 8 g: 2 g to 8 g: 30 mL to 100 mL.
[0012] The above preparation method is further improved. In step S3, the ratio of the aminated magnetic microsphere-carbon-based composite material to the LDH precursor is 100 mg~500 mg: 0.001 mol~0.005 mol; the molar ratio of the soluble divalent metal salt to the soluble trivalent metal salt in the LDH precursor is 1:1; the mass ratio of the aminated magnetic microsphere-carbon-based composite material to urea is 0.1~0.6:1~8.
[0013] The above preparation method is further improved, in step S1, the ratio of the carbon-based material to the iron salt is 250mg-500mg: 0.005mol-0.01mol.
[0014] The above preparation method is further improved. In step S3, the ratio of the aminated magnetic microsphere-carbon-based composite material to the LDH precursor is 200mg-300mg: 0.002mol-0.003mol; the mass ratio of the aminated magnetic microsphere-carbon-based composite material to urea is 0.2-0.4: 3-5.
[0015] The above preparation method is further improved, wherein the carbon-based material is at least one of carbon nanotubes, graphene, activated carbon, biochar, and carbon cloth; before use, the carbon-based material also includes the following treatment: mixing the carbon-based material with water to form a carbon-based material dispersion; the mass concentration of the carbon-based material in the carbon-based material dispersion is 5% (w / v) to 10% (w / v); before use, the carbon nanotubes also include the following treatment: mixing the carbon nanotubes with concentrated nitric acid, stirring for 3h to 6h at 95°C to 110°C, cooling to room temperature, filtering, washing to neutrality, centrifuging at a speed of 5000r / min to 10000r / min for 5min to 10min, and freeze-drying to obtain acidified carbon nanotubes.
[0016] The above preparation method is further improved, wherein the iron salt is at least one of FeCl2, FeCl3, FeSO4, Fe2(SO4)3, Fe(NO3)2, Fe(NO3)3 and (NH4)2Fe(SO4)2·6H2O.
[0017] The above preparation method is further improved, wherein the average molecular weight of the polyvinyl pyrrolidone is 40,000 to 130,000;
[0018] The above preparation method is further improved in that the amination reagent is urea or ammonium acetate.
[0019] The solvent is a mixed solution of polyethylene glycol and / or ethanol / glycerol; the polymerization degree of the polyethylene glycol is 300-1000; in the mixed solution of ethanol / glycerol, the volume ratio of ethanol to glycerol is 1:1.
[0020] The above preparation method is further improved, wherein the divalent metal cations in the soluble divalent metal salt are one or two of Co, Ni, Cu, Zn, Mg, Fe, and Mn; the trivalent metal cations in the soluble trivalent metal salt are one or two of Al, Ni, Fe, Cr, and In; the acid radical ions in the soluble divalent metal salt and the soluble trivalent metal salt are Cl - 、SO4 2- 、NO3 - One or both of the following.
[0021] The above preparation method is further improved in that the carbon-based material is at least one of carbon nanotubes and activated carbon.
[0022] The above preparation method is further improved, wherein the iron salt is at least one of Fe2(SO4)3 and (NH4)2Fe(SO4)2·6H2O.
[0023] The above preparation method is further improved, wherein the molecular weight of the polyvinyl pyrrolidone is 40,000 to 58,000.
[0024] The above preparation method is further improved in that the polymerization degree of the polyethylene glycol is 300-600.
[0025] The above-mentioned preparation method is further improved, wherein the soluble divalent metal salt is one or two of Co(NO3)2, Ni(NO3)2, and MgSO4; the soluble trivalent metal salt is one or two of NH4Al(SO4)2 and Al2(SO4)3.
[0026] The above-mentioned preparation method is further improved. In step S1, the preparation process of the mixed solution A is: dissolving iron salt in a solvent to prepare an iron salt solution, adding carbon-based material, polyvinyl pyrrolidone, sodium acetate, and an amination agent, stirring to obtain a mixed solution A; the stirring is carried out at a temperature of 25°C to 45°C; the stirring speed is 400r / min to 650r / min; and the stirring time is 30min to 120min.
[0027] The above preparation method is further improved. In step S2, the temperature of the hydrothermal reaction is 160°C to 220°C; the time of the hydrothermal reaction is 6h to 12h; after the hydrothermal reaction is completed, the following treatment is also included: the product obtained after the hydrothermal reaction is centrifuged at a speed of 6000r / min to 10000r / min for 5min to 10min, and the product obtained after centrifugation is washed with ethanol solution and deionized water to obtain an aminated magnetic microsphere-carbon-based composite material.
[0028] The above preparation method is further improved. In step S3, the preparation process of the mixed solution B is: adding the aminated magnetic microsphere-carbon-based composite material to deionized water, stirring for 30min to 120min at a temperature of 25°C to 45°C and a rotation speed of 400r / min to 650r / min to prepare an aminated magnetic microsphere-carbon-based composite material dispersion, adding LDH precursor and alkaline substance, stirring to obtain a mixed solution B.
[0029] The above preparation method is further improved, in step S4, the temperature of the hydrothermal reaction is 100°C to 180°C; the time of the hydrothermal reaction is 6h to 36h; after the hydrothermal reaction is completed, the following treatment is also included: the product obtained after the hydrothermal reaction is centrifuged at a speed of 5000r / min to 10000r / min for 5min to 10min, the product obtained after centrifugation is washed with ethanol solution and deionized water, and freeze-dried to obtain an aminated magnetic microsphere-carbon-layered double hydroxide composite material.
[0030] The above preparation method is further improved, in step S1, the stirring is carried out at a temperature of 25°C to 35°C; the stirring speed is 550r / min to 650r / min; and the stirring time is 60min to 90min.
[0031] The above preparation method is further improved. In step S2, the temperature of the hydrothermal reaction is 180°C to 200°C; the time of the hydrothermal reaction is 8h to 10h; the speed of the centrifuge is 8000r / min to 10000r / min; and the time of the centrifugation is 8min to 10min.
[0032] The above preparation method is further improved, in step S3, the stirring is carried out at a temperature of 30°C to 35°C; the stirring speed is 550r / min to 650r / min; and the stirring time is 60min to 90min.
[0033] The above preparation method is further improved, in step S4, the temperature of the hydrothermal reaction is 120° C. to 160° C.; the time of the hydrothermal reaction is 12 h to 36 h.
[0034] As a general inventive concept, the present invention also provides an aminated magnetic microsphere-carbon-based-layered double hydroxide composite material, comprising a carbon-based material, the surface of which is loaded with magnetic microspheres to form an aminated magnetic microsphere-carbon-based composite material; the surface of the aminated magnetic microsphere-carbon-based composite material is loaded with layered double hydroxide; the carbon-based material is at least one of carbon nanotubes, graphene, activated carbon, biochar, and carbon cloth; the carbon nanotubes are multi-walled carbon nanotubes, presenting a multi-layer tubular structure, with a diameter of 8nm to 12nm; the activated carbon and biochar are powdered, with a particle size greater than 200 mesh; the magnetic microspheres are spherical structures or spherical disc structures, with a diameter of 10nm to 100nm.
[0035] The above-mentioned aminated magnetic microsphere-carbon-layered double hydroxide composite material is further improved and is prepared by the above-mentioned preparation method.
[0036] As a general inventive concept, the present invention also provides an application of the above-mentioned aminated magnetic microsphere-carbon-based-layered double hydroxide composite material in treating heavy metal wastewater. In a further improvement, the application comprises the following steps: mixing the aminated magnetic microsphere-carbon-based-layered double hydroxide composite material with heavy metal wastewater, stirring, and completing the treatment of heavy metals in the wastewater; the mass volume ratio of the aminated magnetic microsphere-carbon-based-layered double hydroxide composite material to the heavy metal wastewater is 1 mg to 5 mg: 5 mL to 10 mL; the heavy metal ions in the heavy metal wastewater are Cd 2+ , Pb 2+ , Cu 2+ 、Zn 2+ 、As 3+ Cr 3 + At least one of the following; the initial concentration of heavy metal ions in the heavy metal wastewater is 10 mg / L to 100 mg / L; the pH value of the heavy metal wastewater is 6 to 8; the stirring temperature is 25°C to 45°C; the stirring speed is 160rpm to 220rpm; and the time is 12h to 24h.
[0037] Compared with the prior art, the advantages of the present invention are:
[0038] (1) In view of the defects of the existing carbon-based-LDH composite materials such as unevenness, easy agglomeration, and poor stability, the present invention creatively proposes a method for preparing an aminated magnetic microsphere-carbon-based-layered double hydroxide composite material, firstly using a soft template method to directly form magnetic microspheres with regular morphology on the surface of the carbon-based material in one step, and the aminated magnetic microsphere-carbon-based composite material thus prepared is a magnetized carbon-based material, which can avoid the damage of the magnetic particles to the structure and pores of the carbon material in the traditional preparation method, and can enhance the binding stability of the carbon-based material and the magnetic particles. At the same time, by loading Fe ions on the surface of the carbon-based material in advance, it is beneficial for the LDH precursor to directly bind to the Fe ions on the carbon-based surface, thereby enhancing the binding ability between the carbon-based material and LDH and the stability of the composite material. Subsequently, the aminated magnetic microsphere-carbon-based composite material is mixed with an LDH precursor (a soluble divalent metal salt and / or a soluble trivalent metal salt for preparing layered double hydroxides) and subjected to a hydrothermal reaction under alkaline conditions. During the hydrothermal reaction, the LDH precursor reacts with Fe ions on the surface of the carbon-based material to form a corresponding LDH and is in situ loaded on the aminated magnetic microsphere-carbon-based composite material, which not only enhances the binding ability and stability of LDH and the carbon-based material, but also makes the structure and composition controllable. At the same time, since the carbon-based material has not undergone a drying and redispersion stage, the uniformity of the magnetic microspheres and LDH on the surface of the final material can also be enhanced. The final composite material not only preserves the layered structure of LDH intact, but also can effectively improve the dispersion of LDH and magnetic particles in the carbon material, and preserves the surface properties and functional groups of LDH, magnetic microspheres and carbon-based materials. Compared with the existing conventional preparation method, the aminated magnetic microsphere-carbon-based-layered double hydroxide composite material prepared by the preparation method of the present invention has a larger specific surface area and more adsorption sites, thereby showing more excellent adsorption performance. At the same time, the binding force between different components is stronger, which also makes the composite material have more excellent stability. It is a new carbon-based LDH composite material with excellent adsorption performance, good stability, easy separation and environmental friendliness. It can be used as an adsorbent and is widely used to adsorb heavy metals in water bodies, and can achieve effective removal of heavy metals in water bodies. It has high practical value and broad application prospects in the field of heavy metal pollution control, and has very important practical significance for achieving effective control of heavy metal polluted wastewater. In addition, in the preparation method of the present invention, the morphology and size of the intermediate matrix and the final product of the composite material can be regulated by the source, type, type of template agent, reaction temperature and different soluble salts of carbon materials, and the magnetic microspheres, carbon-based materials and LDH in the preparation process can effectively improve the porosity, specific surface area, functional groups, etc. of the composite material, and can also avoid the shortcomings of large-scale agglomeration of individual materials, few reaction sites, and low specific surface area.In addition, the preparation method of the present invention has the advantages of simple process, controllable process, continuous production, wide source of raw materials and low price, simple operation and reaction conditions, low energy consumption, and no need for special chemical equipment. It is suitable for large-scale preparation and convenient for industrial application.
[0039] (2) In the preparation method of the present invention, in the process of preparing the aminated magnetic microsphere-carbon-based composite material, by optimizing the ratio of the carbon-based material to the iron salt to 100 mg to 500 mg: 0.002 mol to 0.01 mol, in particular, the ratio of the carbon-based material to the iron salt to 250 mg to 500 mg: 0.005 mol to 0.01 mol, it is not only conducive to forming magnetic particles with controllable morphology and size, but also conducive to uniform loading of the magnetic particles on the carbon-based material; by optimizing the ratio of the iron salt to the solvent to 3 mmol to 5 mmol ∶30mL~100mL, the concentration of iron salt in the solvent can be changed, the size of magnetic microspheres and the number of loaded microspheres can be regulated. If the ratio is too high, it is easy to form agglomerations, while too low is not conducive to the formation of regular morphology of microspheres. By optimizing the ratio of polyvinyl pyrrolidone, sodium acetate, amination agent and solvent to 2g~8g∶2g~8g∶2g~8g∶30mL~100mL, the formation of microspheres can be promoted. This is because a too high ratio is easy to affect the formation process of microspheres in the reaction system, while a too low ratio is not conducive to the formation of amination conditions of the reaction system.
[0040] (3) In the preparation method of the present invention, in the process of preparing the aminated magnetic microsphere-carbon-based composite material, a mixed solution of polyethylene glycol and / or ethanol / glycerol is used as a solvent, and in particular, the degree of polymerization of polyethylene glycol is 300 to 1000, so that various precursors in the reaction system can be quickly mixed and can be stably dispersed in the medium solution, thereby facilitating the uniform and stable loading of the magnetic microspheres on the carbon-based material; and, by adding polyvinyl pyrrolidone to the reaction system, in particular, polyvinyl pyrrolidone with an average molecular weight of 40,000 to 130,000 as a surfactant, it is conducive to the formation of smaller-sized magnetic microspheres; in addition, after the carbon-based material, iron salt, polyvinyl pyrrolidone, sodium acetate, amination agent and solvent are mixed, by optimizing the stirring temperature, rate and time, it is conducive to the uniform dispersion of the carbon-based material in the medium and the mixing with Fe in the iron salt. 2+ / Fe 3+ Thorough mixing is more conducive to Fe 2+ / Fe 3+ Evenly loaded on the surface of carbon-based materials.
[0041] (4) In the preparation method of the present invention, during the process of preparing the aminated magnetic microsphere-carbon-based composite material, a mixed solution of the carbon-based material, iron salt, polyvinyl pyrrolidone, sodium acetate, and amination agent is subjected to a hydrothermal reaction at a reaction temperature of 180 to 200° C. for 8 to 10 hours, which is conducive to the formation of hollow structured nano-microspheres. Furthermore, the product after the hydrothermal reaction is centrifuged at a centrifugal speed of 8000 to 10000 r / min for 8 to 10 minutes, which is conducive to the full separation of the product. At the same time, before use, the prepared aminated magnetic microsphere-carbon-based composite material is redispersed in water to form a dispersion, which is more conducive to the uniform dispersion of the composite material in subsequent steps.
[0042] (5) In the preparation method of the present invention, in the process of preparing layered double hydroxide using LDH precursor, by optimizing the ratio of aminated magnetic microspheres-carbon-based composite material to LDH precursor to 100 mg-500 mg: 0.001 mol-0.005 mol, it is beneficial to form LDH on the surface of carbon-based composite material. If the ratio is too high, LDH is not tightly bound to the carbon-based composite material or is wrapped by the carbon-based material, while too low a ratio will lead to the formation of too much LDH, which is not conducive to the performance of carbon-based material. By optimizing the mass ratio of aminated magnetic microspheres-carbon-based composite material to urea to 0.1-0.6: 1-8, effective alkaline conditions can be guaranteed to promote the formation of LDH, while too high a ratio is not conducive to the formation of effective alkaline conditions, and too low a ratio affects the loading of LDH on the aminated magnetic microspheres-carbon-based composite material.
[0043] (6) In the preparation method of the present invention, urea is used as an alkaline substance and aminating agent, which can increase the functional groups on the surface of the magnetic microspheres and the carbon-based materials and enhance their binding ability with LDH, which is beneficial to the stability and reactivity of the composite material. At the same time, the carbon-based material enhances the dispersion performance of the magnetic microspheres and LDH, and improves the mechanical properties, electrical conductivity and stability of the material.
[0044] (7) The present invention also provides an application of an aminated magnetic microsphere-carbon-based-layered double hydroxide composite material in treating heavy metal wastewater. Taking heavy metal cadmium wastewater as an example, by mixing the aminated magnetic microsphere-carbon-based-layered double hydroxide composite material with heavy metal cadmium wastewater and stirring, the heavy metal cadmium in the wastewater can be quickly and thoroughly removed. The invention has the advantages of convenient operation, high treatment efficiency, good removal effect, etc., and is of great significance for effectively removing heavy metals in water bodies. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0046] Figure 1This is a SEM image of the aminated magnetic microsphere-activated carbon-layered double hydroxide composite material (Fe(NH4)-AC-(FeCo)LDH-120°C) prepared in Example 1 of the present invention.
[0047] Figure 2 This is a SEM image of the aminated magnetic microsphere-carbon nanotube-layered double hydroxide composite material (Fe(NH4)-CNTs-(FeCo)LDH-120°C) prepared in Example 1 of the present invention.
[0048] Figure 3 This is a SEM image of the aminated magnetic microsphere-activated carbon-layered double hydroxide composite material (Fe(NH4)-AC-(FeCo)LDH-180°C) prepared in Example 2 of the present invention.
[0049] Figure 4 This is a SEM image of the aminated magnetic microsphere-carbon nanotube-layered double hydroxide composite material (Fe(NH4)-CNTs-(FeCo)LDH-180°C) prepared in Example 2 of the present invention.
[0050] Figure 5 It is the Fourier transform infrared spectra of the aminated magnetic microspheres-activated carbon-layered double hydroxide composite materials (Fe(NH4)-AC-(FeCo)LDH-120℃, Fe(NH4)-AC-(FeCo)LDH-180℃) prepared in Examples 1 and 2 of the present invention.
[0051] Figure 6 These are Fourier transform infrared spectra of the aminated magnetic microspheres-carbon nanotubes-layered double hydroxide composite materials (Fe(NH4)-CNTs-(FeCo)LDH-120°C, Fe(NH4)-CNTs-(FeCo)LDH-180°C) prepared in Examples 1 and 2 of the present invention.
[0052] Figure 7 These are the XRD patterns of the aminated magnetic microspheres-activated carbon-layered double hydroxide composite materials (Fe(NH4)-AC-(FeCo)LDH-120°C, Fe(NH4)-AC-(FeCo)LDH-180°C) and the aminated magnetic microspheres-carbon nanotubes-layered double hydroxide composite materials (Fe(NH4)-CNTs-(FeCo)LDH-120°C, Fe(NH4)-CNTs-(FeCo)LDH-180°C) prepared in Examples 1 and 2 of the present invention.
[0053] Figure 8 This is a SEM image of the aminated magnetic microsphere-activated carbon-layered double hydroxide composite material (Fe(NH4)-AC-(CoAl)LDH) prepared in Example 3 of the present invention.
[0054] Fig. 9 This is a SEM image of the aminated magnetic microsphere-carbon nanotube-layered double hydroxide composite material (Fe(NH4)-CNTs-(CoAl)LDH) prepared in Example 3 of the present invention.
[0055] Fig.10 This is a SEM image of the aminated magnetic microsphere-activated carbon-layered double hydroxide composite material (Fe(NH4)-AC-(NiAl)LDH) prepared in Example 3 of the present invention.
[0056] Fig.11 This is a SEM image of the aminated magnetic microsphere-carbon nanotube-layered double hydroxide composite material (Fe(NH4)-CNTs-(NiAl)LDH) prepared in Example 3 of the present invention.
[0057] Fig.12 This is a Fourier transform infrared spectrum of the aminated magnetic microsphere-carbon nanotube-layered double hydroxide composite materials (Fe(NH4)-CNTs-(CoAl)LDH, Fe(NH4)-CNTs-(NiAl)LDH) prepared in Example 3 of the present invention.
[0058] Fig.13 This is the Fourier transform infrared spectrum of the aminated magnetic microsphere-activated carbon-layered double hydroxide composite materials (Fe(NH4)-AC-(CoAl)LDH, Fe(NH4)-AC-(NiAl)LDH) prepared in Example 3 of the present invention.
[0059] Fig.14 These are the XRD patterns of the aminated magnetic microspheres-carbon nanotubes-layered double hydroxide composites (Fe(NH4)-CNTs-(CoAl)LDH, Fe(NH4)-CNTs-(NiAl)LDH) and the aminated magnetic microspheres-activated carbon-layered double hydroxide composites (Fe(NH4)-AC-(CoAl)LDH, Fe(NH4)-AC-(NiAl)LDH) prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0060] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby.
[0061] In the following examples, unless otherwise specified, the materials and instruments used are commercially available, the processes used are conventional processes, the equipment used are conventional equipment, and the data obtained are the average values of more than three repeated experiments.
[0062] Example 1
[0063] A method for preparing an aminated magnetic microsphere-carbon-based-layered double hydroxide composite material, specifically using carbon nanotubes and activated carbon as carbon-based materials to prepare an aminated magnetic microsphere-carbon nanotube-layered double hydroxide composite material (Fe(NH4)-CNTs-(FeCo)LDH-120°C) and an aminated magnetic microsphere-activated carbon-layered double hydroxide composite material (Fe(NH4)-AC-(FeCo)LDH-120°C), respectively, comprising the following steps:
[0064] (1) Preparation of aminated magnetic microsphere-carbon-based composites
[0065] (1.1) Add carbon nanotubes (the carbon nanotubes are multi-walled carbon nanotubes, with a multi-layer tubular structure, a diameter of 8 nm to 12 nm, and are commercially available) to concentrated nitric acid, stir at 95°C for 6 h, cool to room temperature, filter and wash with deionized water until neutral, centrifuge at 8000 r / min for 5 min, and freeze-dry to obtain acidified carbon nanotubes. Subsequently, the acidified carbon nanotubes are ultrasonically dispersed in deionized water to obtain a carbon nanotube dispersion of 5% (w / v).
[0066] Activated carbon (powdered, particle size > 200 mesh, commercially available) was ultrasonically dispersed in deionized water, and the precipitate was removed after standing for 6 hours. The upper dispersion was centrifuged at 8000 r / min for 5 minutes, and the centrifuged product was redispersed to make the activated carbon concentration in the dispersion 5% (w / v) to obtain an activated carbon dispersion.
[0067] (1.2) According to the ratio of iron salt to solvent of 5mmol:60mL, Fe(NO3)3·9H2O was dissolved in 60mL of polyethylene glycol with a degree of polymerization of 300, and the mixture was stirred evenly at a speed of 600r / min to obtain an iron salt solution; according to the addition ratio of dispersion liquid to Fe(NO3)3·9H2O of 10mL:5mmol, carbon nanotube dispersion liquid and activated carbon dispersion liquid were added to the iron salt solution respectively, and polyvinyl pyrrolidone (PVP), sodium acetate and urea were added at the same time, wherein the addition ratio of PVP, sodium acetate, urea and polyethylene glycol was 3g:5g:3g:60mL, and stirring was continued for 2h until the color changed from yellow-brown to black, and a mixed solution A containing carbon nanotubes and a mixed solution A containing activated carbon were obtained respectively.
[0068] (1.3) The two mixed solutions A were transferred to 100 mL autoclaves respectively and kept at 180°C for 10 h. After the autoclave temperature dropped to room temperature, the reaction solution was centrifuged at 6000 r / min for 5 min. The obtained centrifugal product was washed with 50% ethanol solution and deionized water for 3 times each, and freeze-dried to obtain an aminated magnetic microsphere-carbon nanotube composite material and an aminated magnetic microsphere-activated carbon composite material. The aminated magnetic microsphere-carbon nanotube composite material and the aminated magnetic microsphere-activated carbon composite material were dispersed again in deionized water to make the composite material concentration in the dispersion liquid 5% (w / v), to obtain an aminated magnetic microsphere-carbon nanotube composite material dispersion liquid and an aminated magnetic microsphere-activated carbon composite material dispersion liquid.
[0069] (2) Preparation of aminated magnetic microsphere-carbon-based layered double hydroxide composites
[0070] (2.1) Dissolve 2 mmol of soluble divalent metal salt (cobalt nitrate (Co(NO3)2+6H2O) and 2 mmol of soluble trivalent metal salt (Fe(NO3)3·9H2O) and 5 g of urea in 60 mL of deionized water, and stir continuously at a temperature of 25°C and a rotation speed of 550 r / min. At the same time, add 5 mL of aminated magnetic microsphere-carbon nanotube composite material dispersion and aminated magnetic microsphere-activated carbon composite material dispersion, and continue stirring for 1.5 h to obtain a mixed solution B containing aminated magnetic microsphere-carbon nanotube composite material and a mixed solution B containing aminated magnetic microsphere-activated carbon composite material, respectively.
[0071] (2.2) The two mixed solutions B were transferred to a reactor and kept at 120°C for 36 hours. The obtained products were centrifuged at 5000 r / min for 5 minutes. The obtained centrifuged products were washed with 50% ethanol solution and deionized water for 3 times each, and freeze-dried to obtain aminated magnetic microspheres-carbon nanotubes-layered double hydroxide composite materials and aminated magnetic microspheres-activated carbon-layered double hydroxide composite materials, which were respectively recorded as Fe(NH4)-CNTs-(FeCo)LDH-120°C and Fe(NH4)-AC-(FeCo)LDH-120°C.
[0072] The aminated magnetic microsphere-carbon nanotube-layered double hydroxide composite material (Fe(NH4)-CNTs-(FeCo)LDH-120°C) prepared in this embodiment includes a carbon-based material, and magnetic microspheres are loaded on the surface of the carbon-based material to form an aminated magnetic microsphere-carbon-based composite material, and the surface of the aminated magnetic microsphere-carbon-based composite material is loaded with layered double hydroxide, wherein the carbon-based material is carbon nanotubes, which have a multi-layer tubular structure and a size of 8nm to 12nm, and the magnetic microspheres have a spherical structure and a diameter of 10nm to 100nm (see Figure 1), the layered double hydroxide is iron-cobalt layered double hydroxide (FeCo-LDH).
[0073] The aminated magnetic microsphere-activated carbon-layered double hydroxide composite material (Fe(NH4)-AC-(FeCo)LDH-120°C) prepared in this embodiment includes a carbon-based material, the surface of the carbon-based material is loaded with magnetic microspheres to form an aminated magnetic microsphere-carbon-based composite material, the surface of the aminated magnetic microsphere-carbon-based composite material is loaded with layered double hydroxide, wherein the carbon-based material is activated carbon, powdered, and has a particle size of >200 mesh; the magnetic microspheres are disc-shaped, and the diameter size is between 10nm and 100nm. Figure 2 , the layered double hydroxide is iron-cobalt layered double hydroxide (FeCo-LDH).
[0074] Figure 1 This is a SEM image of the aminated magnetic microsphere-activated carbon-layered double hydroxide composite material (Fe(NH4)-AC-(FeCo)LDH-120℃) prepared in Example 1 of the present invention. Figure 1 It can be seen that the SEM results show that in the aminated magnetic microspheres-activated carbon-layered double hydroxide composite material (Fe(NH4)-AC-(FeCo)LDH-120℃), the iron cobalt layered double hydroxide (FeCo-LDH) presents an obvious layered structure, and the activated carbon (AC) is tightly combined with the iron cobalt layered double hydroxide (FeCo-LDH), presenting a porous structure, and Fe particles with a size of 8 to 10 nm are distributed on the surface of the aminated magnetic microspheres-activated carbon-layered double hydroxide composite material (Fe(NH4)-AC-(FeCo)LDH-120℃), and there are no obvious agglomerates.
[0075] Figure 2 This is a SEM image of the aminated magnetic microsphere-carbon nanotube-layered double hydroxide composite material (Fe(NH4)-CNTs-(FeCo)LDH-120℃) prepared in Example 1 of the present invention. Figure 2 It can be seen that the SEM results show that the iron-cobalt layered double hydroxide (FeCo-LDH) in the aminated magnetic microspheres-carbon nanotubes-layered double hydroxide composite material (Fe(NH4)-CNTs-(FeCo)LDH-120℃) presents an obvious layered structure, and at the same time, the surface of the iron-cobalt layered double hydroxide (FeCo-LDH) is inlaid or loaded with a large number of evenly dispersed disc-shaped Fe microspheres and carbon nanotubes, and there are no obvious agglomerates.
[0076] Example 2
[0077] A method for preparing an aminated magnetic microsphere-carbon-based layered double hydroxide composite material, specifically investigating the effect of different LDH reaction temperatures on the morphology of the composite material, comprises the following steps:
[0078] (1) Preparation of aminated magnetic microsphere-carbon-based composite materials
[0079] (1.1) Add carbon nanotubes (the carbon nanotubes are multi-walled carbon nanotubes, with a multi-layer tubular structure, a diameter of 8 nm to 12 nm, and are commercially available) to concentrated nitric acid, stir at 95°C for 6 h, cool to room temperature, filter and wash with deionized water until neutral, centrifuge at 8000 r / min for 5 min, and freeze-dry to obtain acidified carbon nanotubes. Subsequently, the acidified carbon nanotubes are ultrasonically dispersed in deionized water to obtain a carbon nanotube dispersion of 10% (w / v).
[0080] Activated carbon (in powder form, with a particle size of >200 mesh) was ultrasonically dispersed in deionized water, and the precipitate was removed after standing for 6 hours. The upper dispersion was centrifuged at 8000 r / min for 5 minutes, and the centrifuged product was redispersed to make the activated carbon concentration in the dispersion 10% (w / v) to obtain an activated carbon dispersion.
[0081] (1.2) According to the ratio of iron salt to solvent of 3mmol:60mL, Fe(NO3)3·9H2O was dissolved in 60mL of polyethylene glycol with a polymerization degree of 400, and the mixture was stirred evenly at a speed of 600r / min to obtain an iron salt solution; according to the addition ratio of dispersion liquid and Fe(NO3)3·9H2O of 10mL:3mmol, carbon nanotubes or dispersion liquid activated carbon dispersion was added to the iron salt solution, and polyvinyl pyrrolidone (PVP), sodium acetate and urea were added at the same time, wherein the addition ratio of PVP, sodium acetate, urea and polyethylene glycol was 3g:6g:4g:60mL, and stirring was continued for 2h, and the color changed from yellow-brown to black, and a mixed solution A containing carbon nanotubes and a mixed solution A containing activated carbon were obtained respectively.
[0082] (1.3) The two mixed solutions A were transferred to a 100 mL autoclave, respectively, and kept at 180°C for 10 h. After the autoclave temperature dropped to room temperature, the reaction solution was centrifuged at 6000 r / min for 5 min. The obtained centrifugal product was washed with 50% ethanol solution and deionized water for 3 times, respectively, and freeze-dried to obtain an aminated magnetic microsphere-carbon nanotube composite material and an aminated magnetic microsphere-activated carbon composite material. The aminated magnetic microsphere-carbon nanotube composite material and the aminated magnetic microsphere-activated carbon composite material were dispersed again in deionized water to make the composite material concentration in the dispersion liquid 5% (w / v), to obtain an aminated magnetic microsphere-carbon nanotube composite material dispersion liquid and an aminated magnetic microsphere-activated carbon composite material dispersion liquid.
[0083] (2) Preparation of aminated magnetic microsphere-carbon-based layered double hydroxide composites
[0084] (2.1) Dissolve 2 mmol of soluble divalent metal salt (cobalt nitrate (Co(NO3)2·6H2O) and 2 mmol of soluble trivalent metal salt (Fe(NO3)3·9H2O) and 5 g of urea in 60 mL of deionized water, and stir continuously at a temperature of 25°C and a rotation speed of 550 r / min. At the same time, add 5 mL of aminated magnetic microsphere-carbon nanotube composite material dispersion and aminated magnetic microsphere-activated carbon composite material dispersion respectively, and stir continuously for 1 hour to obtain a mixed solution B containing aminated magnetic microsphere-carbon nanotube composite material and a mixed solution B containing aminated magnetic microsphere-activated carbon composite material.
[0085] (2.2) The two mixed solutions B were transferred to the reactor respectively and kept at 180°C for 12 h. The obtained products were centrifuged at 6000 r / min for 5 min. The obtained centrifuged products were washed with 50% ethanol solution and deionized water for 3 times respectively and freeze-dried to obtain aminated magnetic microspheres-carbon nanotubes-layered double hydroxide composite materials and aminated magnetic microspheres-activated carbon-layered double hydroxide composite materials, which were recorded as Fe(NH4)-CNTs-(FeCo)LDH-180°C and Fe(NH4)-AC-(FeCo)LDH-180°C, respectively.
[0086] The aminated magnetic microspheres-carbon nanotubes-layered double hydroxide composite material (Fe(NH4)-CNTs-(FeCo)LDH-180℃) prepared in this embodiment includes a carbon-based material, the surface of the carbon-based material is loaded with magnetic microspheres to form an aminated magnetic microspheres-carbon-based composite material, the surface of the aminated magnetic microspheres-carbon-based composite material is loaded with layered double hydroxides, wherein the carbon-based material is carbon nanotubes (with a multi-layer tubular structure and a size of 8nm to 12nm); the magnetic microspheres are spherical in structure and have a size of 10nm to 100nm, and the layered double hydroxide is an iron-cobalt layered double hydroxide (FeCo-LDH).
[0087] The aminated magnetic microspheres-carbon nanotubes-layered double hydroxide composite material (Fe(NH4)-AC-(FeCo)LDH-180°C) prepared in this embodiment includes a carbon-based material, the surface of the carbon-based material is loaded with magnetic microspheres to form an aminated magnetic microsphere-carbon-based composite material, the surface of the aminated magnetic microsphere-carbon-based composite material is loaded with layered double hydroxide, wherein the carbon-based material is activated carbon (in powder form, with a particle size of >200 mesh); the magnetic microspheres are spherical in structure, with a size of 10nm to 100nm, and the layered double hydroxide is an iron-cobalt layered double hydroxide (FeCo-LDH).
[0088] Figure 3This is a SEM image of the aminated magnetic microsphere-activated carbon-layered double hydroxide composite material (Fe(NH4)-AC-(FeCo)LDH-180℃) prepared in Example 2 of the present invention. Figure 3 It can be seen that the SEM results show that the Fe species on the aminated magnetic microspheres-activated carbon-layered double hydroxide composite material (Fe(NH4)-AC-(FeCo)LDH-180℃) are spherical and tightly bound to the activated carbon (AC) on the surface of iron-cobalt layered double hydroxide (FeCo-LDH).
[0089] Figure 4 This is a SEM image of the aminated magnetic microsphere-carbon nanotube-layered double hydroxide composite material (Fe(NH4)-CNTs-(FeCo)LDH-180℃) prepared in Example 2 of the present invention. Figure 4 It can be seen that the SEM results show that the Fe species on the aminated magnetic microspheres-activated carbon-layered double hydroxide composite material (Fe(NH4)-CNTs-(FeCo)LDH-180℃) is disc-shaped and is alternately loaded with carbon nanotubes (CNTs) on the surface of iron-cobalt layered double hydroxide (FeCo-LDH). The iron-cobalt layered double hydroxide (FeCo-LDH) presents a tightly stacked layered structure.
[0090] Figure 5 It is the Fourier transform infrared spectra of the aminated magnetic microspheres-activated carbon-layered double hydroxide composite materials (Fe(NH4)-AC-(FeCo)LDH-120℃, Fe(NH4)-AC-(FeCo)LDH-180℃) prepared in Examples 1 and 2 of the present invention.
[0091] Figure 6 These are Fourier transform infrared spectra of the aminated magnetic microspheres-carbon nanotubes-layered double hydroxide composite materials (Fe(NH4)-CNTs-(FeCo)LDH-120°C, Fe(NH4)-CNTs-(FeCo)LDH-180°C) prepared in Examples 1 and 2 of the present invention.
[0092] Depend on Figure 5 and Figure 6It can be seen that compared with the aminated magnetic microspheres-carbon nanotubes-layered double hydroxide composites (Fe(NH4)-CNTs-(FeCo)LDH-120℃, Fe(NH4)-CNTs-(FeCo)LDH-180℃), the aminated magnetic microspheres-carbon nanotubes-layered double hydroxide composites (Fe(NH4)-AC-(FeCo)LDH-120℃, Fe(NH4)-AC-(FeCo)LDH-180℃) show a significant absorption peak at 3881.41, indicating that they have more abundant hydroxyl groups, etc., and there are inconspicuous characteristic peaks at around 3000, indicating the presence of CN bonds in the material. In addition, compared with Fe(NH4)-AC-(FeCo)LDH-120℃ and Fe(NH4)-CNTs-(FeCo)LDH-120℃ prepared at 120℃, the absorption peak at 3881.41 of Fe(NH4)-AC-(FeCo)LDH-180℃ and Fe(NH4)-CNTs-(FeCo)LDH-180℃ prepared at 180℃ in the present invention disappears, but the intensities of other absorption peaks are higher, indicating that the change in the dipole moment of the groups on Fe(NH4)-AC-(FeCo)LDH-180℃ and Fe(NH4)-CNTs-(FeCo)LDH-180℃ during the stretching vibration process increases.
[0093] Figure 7 These are the XRD patterns of the aminated magnetic microspheres-activated carbon-layered double hydroxide composite materials (Fe(NH4)-AC-(FeCo)LDH-120°C, Fe(NH4)-AC-(FeCo)LDH-180°C) and the aminated magnetic microspheres-carbon nanotubes-layered double hydroxide composite materials (Fe(NH4)-CNTs-(FeCo)LDH-120°C, Fe(NH4)-CNTs-(FeCo)LDH-180°C) prepared in Examples 1 and 2 of the present invention.
[0094] Depend on Figure 7It can be seen that the characteristic peaks of the aminated magnetic microspheres-activated carbon-layered double hydroxide composites (Fe(NH4)-AC-(FeCo)LDH-120℃, Fe(NH4)-AC-(FeCo)LDH-180℃) and the aminated magnetic microspheres-carbon nanotubes-layered double hydroxide composites (Fe(NH4)-CNTs-(FeCo)LDH-120℃, Fe(NH4)-CNTs-(FeCo)LDH-180℃) are very sharp at (006), (101), (107) and (1010), and the peak intensities of (006) and (101) are relatively high, indicating that the structures of Fe microspheres and LDH are regular and the crystallinity is high. At the same time, compared with Fe(NH4)-AC-(FeCo)LDH-180℃ and Fe(NH4)-CNTs-(FeCo)LDH-180℃ prepared at 180℃, Fe(NH4)-CNTs-(FeCo)LDH-120℃ and Fe(NH4)-AC-(FeCo)LDH-120℃ prepared at 120℃ have better crystallinity.
[0095] Example 3
[0096] A method for preparing an aminated magnetic microsphere-carbon-layered double hydroxide composite material, specifically investigating the effects of the amount of magnetic microsphere precursor reagent and different LDH precursor reagents on the morphology of the composite material, comprises the following steps:
[0097] (1) Preparation of aminated magnetic microsphere-carbon-based composite materials
[0098] (1.1) Add carbon nanotubes (the carbon nanotubes are multi-walled carbon nanotubes, with a multi-layer tubular structure, a size of 8 nm to 12 nm, and are commercially available) to concentrated nitric acid, stir at 95°C for 6 h, cool to room temperature, filter and wash with deionized water until neutral, centrifuge at 8000 r / min for 5 min, and freeze-dry to obtain acidified carbon nanotubes. Subsequently, the acidified carbon nanotubes are ultrasonically dispersed in deionized water so that the concentration of carbon nanotubes in the dispersion is 5% (w / v), to obtain a carbon nanotube dispersion.
[0099] Activated carbon (in powder form, with a particle size of >200 mesh) was ultrasonically dispersed in deionized water, and the precipitate was removed after standing for 6 hours. The upper dispersion was centrifuged at 8000 r / min for 5 minutes, and the centrifuged product was redispersed to make the activated carbon concentration in the dispersion 5% (w / v) to obtain an activated carbon dispersion.
[0100] (1.2) According to the ratio of iron salt to solvent of 5mmol:60mL, Fe(NO3)3·9H2O was dissolved in 60mL of polyethylene glycol with a degree of polymerization of 300, and the mixture was stirred evenly at a speed of 600r / min to obtain an iron salt solution; according to the addition ratio of dispersion liquid to Fe(NO3)3·9H2O of 10mL:5mmol, carbon nanotube dispersion liquid and activated carbon dispersion liquid were added to the iron salt solution respectively, and polyvinyl pyrrolidone (PVP), sodium acetate and urea were added at the same time, wherein the addition ratio of PVP, sodium acetate, urea and polyethylene glycol was 3g:6g:4g:60mL, and stirring was continued for 2h until the color changed from yellow-brown to black, and a mixed solution A containing carbon nanotubes and a mixed solution A containing activated carbon were obtained respectively.
[0101] (1.3) The two mixed solutions A were transferred to 100 mL autoclaves respectively and kept at 180°C for 10 h. After the autoclave temperature dropped to room temperature, the reaction solution was centrifuged at 6000 r / min for 5 min. The obtained centrifugal product was washed with 50% ethanol solution and deionized water for 3 times each, and freeze-dried to obtain an aminated magnetic microsphere-carbon nanotube composite material and an aminated magnetic microsphere-activated carbon composite material. The aminated magnetic microsphere-carbon nanotube composite material and the aminated magnetic microsphere-activated carbon composite material were dispersed again in deionized water to make the composite material concentration in the dispersion liquid 5% (w / v), to obtain an aminated magnetic microsphere-carbon nanotube composite material dispersion liquid and an aminated magnetic microsphere-activated carbon composite material dispersion liquid.
[0102] (2) Preparation of aminated magnetic microsphere-carbon-based layered double hydroxide composites
[0103] (2.1) Prepare LDH precursor in the following manner:
[0104] ① Dissolve 3mmol of soluble divalent metal salt nickel nitrate (Ni(NO3)2·6H2O), 3mmol of soluble trivalent metal salt (ammonium aluminum sulfate (NH4Al(SO4)2·12H2O)) and 5g of urea in 60mL of deionized water, that is, the addition ratio of divalent and trivalent metal salts and urea is 3mmol:3mmol:5g.
[0105] ② Dissolve 3mmol of soluble divalent metal salt cobalt nitrate (Co(NO3)2·6H2O), 3mmol of soluble trivalent metal salt (ammonium aluminum sulfate (NH4Al(SO4)2·12H2O)) and 5g of urea in 60mL of deionized water, that is, the addition ratio of divalent and trivalent metal salts and urea is 3mmol:3mmol:5g.
[0106] (2.2) The above-mentioned LDH precursor was continuously stirred at a temperature of 25°C and a rotation speed of 550 r / min, and 5 mL of aminated magnetic microspheres-carbon nanotube composite material dispersion and aminated magnetic microspheres-activated carbon composite material dispersion were added respectively, and the stirring was continued for 2 h to obtain a mixed solution B containing different aminated magnetic microspheres-carbon nanotube composite materials and aminated magnetic microspheres-activated carbon composite materials.
[0107] (2.3) The different mixed solutions B were transferred to the reactor respectively and kept at 120°C for 36 hours. The obtained products were centrifuged at 5000 r / min for 5 minutes. The obtained centrifuged products were washed with 50% ethanol solution and deionized water for 3 times respectively, and freeze-dried to obtain aminated magnetic microspheres-carbon nanotubes-layered double hydroxide composite materials and aminated magnetic microspheres-activated carbon-layered double hydroxide composite materials, which were respectively recorded as Fe(NH4)-CNTs-(CoAl)LDH, Fe(NH4)-AC-(CoAl)LDH and Fe(NH4)-CNTs-(NiAl)LDH, Fe(NH4)-AC-(NiAl)LDH.
[0108] Figure 8 This is a SEM image of the aminated magnetic microsphere-activated carbon-layered double hydroxide composite material (Fe(NH4)-AC-(CoAl)LDH) prepared in Example 3 of the present invention. Figure 8 It can be seen that the SEM results show that the surface of the aminated magnetic microspheres-activated carbon-layered double hydroxide composite material (Fe(NH4)-AC-(CoAl)LDH) presents more and more regular aminated Fe microspheres, which are tightly combined with the activated carbon on the surface of (CoAl)LDH, and the Fe microspheres are evenly distributed without obvious agglomeration.
[0109] Fig. 9 This is a SEM image of the aminated magnetic microsphere-carbon nanotube-layered double hydroxide composite material (Fe(NH4)-CNTs-(CoAl)LDH) prepared in Example 3 of the present invention. Fig. 9 It can be seen that the SEM results show that the Fe microspheres on the aminated magnetic microspheres-activated carbon-layered double hydroxide composite material (Fe(NH4)-CNTs-(CoAl)LDH) are disc-shaped, and the carbon nanotubes are loaded on the surface of (CoAl)LDH, with uniform distribution but certain local agglomeration.
[0110] Fig.10 This is a SEM image of the aminated magnetic microsphere-activated carbon-layered double hydroxide composite material (Fe(NH4)-AC-(NiAl)LDH) prepared in Example 3 of the present invention.
[0111] Fig.11This is a SEM image of the aminated magnetic microsphere-carbon nanotube-layered double hydroxide composite material (Fe(NH4)-CNTs-(NiAl)LDH) prepared in Example 3 of the present invention.
[0112] Depend on Fig.10 and Fig.11 It can be seen that the SEM results show that in the aminated magnetic microspheres-activated carbon-layered double hydroxide composites (Fe(NH4)-AC-(NiAl)LDH) and the aminated magnetic microspheres-carbon nanotubes-layered double hydroxide composites (Fe(NH4)-CNTs-(NiAl)LDH), the morphology of the magnetic microspheres is slightly messy, some of them are not regular spherical or disc-shaped, and the layered double hydroxide structure is not obvious.
[0113] Fig.12 This is a Fourier transform infrared spectrum of the aminated magnetic microsphere-carbon nanotube-layered double hydroxide composite materials (Fe(NH4)-CNTs-(CoAl)LDH, Fe(NH4)-CNTs-(NiAl)LDH) prepared in Example 3 of the present invention.
[0114] Fig.13 This is the Fourier transform infrared spectrum of the aminated magnetic microsphere-activated carbon-layered double hydroxide composite materials (Fe(NH4)-AC-(CoAl)LDH, Fe(NH4)-AC-(NiAl)LDH) prepared in Example 3 of the present invention.
[0115] Depend on Fig.12 and Fig.13 It can be seen that the four composite materials of aminated magnetic microspheres-carbon nanotubes-layered double hydroxide composite materials (Fe(NH4)-CNTs-(CoAl)LDH, Fe(NH4)-CNTs-(NiAl)LDH), aminated magnetic microspheres-activated carbon-layered double hydroxide composite materials (Fe(NH4)-AC-(CoAl)LDH, Fe(NH4)-AC-(NiAl)LDH) have significant absorption peaks near 1350, 1380, 3420, etc., indicating that they have abundant hydroxyl, amine and other groups. However, combined with the characterization results of SEM and XRD, the functional groups of Fe(NH4)-CNTs-(NiAl)LDH and Fe(NH4)-AC-(NiAl)LDH may be hydroxyl and other groups in the amorphous structure of the composite materials.
[0116] Fig.14These are the XRD patterns of the aminated magnetic microspheres-carbon nanotubes-layered double hydroxide composites (Fe(NH4)-CNTs-(CoAl)LDH, Fe(NH4)-CNTs-(NiAl)LDH) and the aminated magnetic microspheres-activated carbon-layered double hydroxide composites (Fe(NH4)-AC-(CoAl)LDH, Fe(NH4)-AC-(NiAl)LDH) prepared in Example 3 of the present invention.
[0117] Depend on Fig.14 It can be seen that the characteristic peaks of aminated magnetic microspheres-carbon nanotubes-layered double hydroxide composites (Fe(NH4)-CNTs-(CoAl)LDH, Fe(NH4)-CNTs-(NiAl)LDH) and aminated magnetic microspheres-activated carbon-layered double hydroxide composites (Fe(NH4)-AC-(CoAl)LDH, Fe(NH4)-AC-(NiAl)LDH) are very sharp at (003), (006), (012), and the peak intensity of (003) is relatively high, indicating that the Fe microspheres and LDH in these materials have regular structures and high crystallinity. Compared with Fe(NH4)-CNTs-(CoAl)LDH, Fe(NH4)-CNTs-(NiAl)LDH has sharp characteristic peaks at (006), (101), (009), (107), and high peak intensity, indicating that the Fe microspheres and LDH in this material have regular structures and high crystallinity. Compared with Fe(NH4)-CNTs-(CoAl)LDH or Fe(NH4)-AC-(CoAl)LDH, the peak widths of the characteristic peaks at (003), (006), and (012) of Fe(NH4)-CNTs-(NiAl)LDH and Fe(NH4)-AC-(NiAl)LDH are increased, and the intensity of the characteristic peaks is decreased, indicating that their crystallinity is reduced.
[0118] Embodiment 4:
[0119] An application of an aminated magnetic microsphere-carbon-based-layered double hydroxide composite material in treating heavy metal wastewater comprises the following steps:
[0120] 1) The aminated magnetic microsphere-carbon-based-layered double hydroxide composite materials prepared in Examples 1 to 3 (Fe(NH4)-AC-(FeCo)LDH-180°C, Fe(NH4)-AC-(FeCo)LDH-120°C, Fe(NH4)-AC-(CoAl)LDH) and the original carbon material were used as adsorbents.
[0121] 2) The aminated magnetic microsphere-activated carbon-layered double hydroxide composite material is applied to the treatment of heavy metal Cd. This embodiment includes the following steps: diluting 1000 mg / L of Cd stock solution into a Cd solution with an initial concentration of 100 mg / L, adjusting the pH value of the heavy metal solution to about 7, adding 50 mg of different adsorbents respectively, placing each treatment group in a water bath constant temperature oscillating box, maintaining the system temperature at 25 ° C, and the oscillation rate at 220 rpm. After 24 hours of reaction, take out each treatment group, place a magnet under each group of conical flasks, separate and absorb the supernatant for filtration, take 0.5 mL of the filtrate, acidify and dilute to 9 mL, use ICP-MS to measure the Cd concentration in the dilution, and calculate the adsorption amount. The results are shown in Table 1.
[0122] 3) The test results show that the Fe(NH4)-AC-LDH composite materials prepared in Examples 1 to 3 have significantly improved the adsorption capacity of heavy metal Cd in water (25.79% to 153.22%), as shown in Table 1.
[0123] Table 1: Removal effect of aminated magnetic microspheres-AC-layered double hydroxide composites and initial AC materials on Cd removal in water
[0124]
[0125] Based on the above results, compared with the existing conventional preparation method, the aminated magnetic microsphere-carbon-based-layered double hydroxide composite material prepared by the preparation method of the present invention has a larger specific surface area and more adsorption sites, thereby showing a more excellent adsorption performance. At the same time, the binding force between different components is stronger, which also makes the composite material have a more excellent stability. It is a new carbon-based LDH composite material with excellent adsorption performance, good stability, easy separation, and environmental friendliness. It can be used as an adsorbent and is widely used to adsorb heavy metals in water bodies, and can achieve effective removal of heavy metals in water bodies. It has a high practical value and a wide range of application prospects in the field of heavy metal pollution control, and has very important practical significance for achieving effective control of heavy metal-contaminated wastewater. In addition, in the preparation method of the present invention, the morphology and size of the intermediate matrix and the final product of the composite material can be regulated by the source, type, type of template agent, reaction temperature and different soluble salts of carbon materials, and the magnetic microspheres, carbon-based materials and LDH in the preparation process can effectively improve the porosity, specific surface area, functional groups, etc. of the composite material, and can also avoid the shortcomings of large-scale agglomeration of individual materials, few reaction sites, and low specific surface area. In addition, the preparation method of the present invention has the advantages of simple process, controllable process, continuous production, wide source of raw materials and low price, simple operation and reaction conditions, low energy consumption, and no need for special chemical equipment. It is suitable for large-scale preparation and convenient for industrial application.
[0126] The above is only a preferred embodiment of the present invention, but it is not intended to limit the present invention. Any person skilled in the art can make many possible changes and modifications to the technical solution of the present invention using the methods and technical contents disclosed above. Therefore, any simple modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of protection of the technical solution of the present invention.
Claims
1. A method for preparing an aminated magnetic microsphere-carbon-based layered double hydroxide composite material, characterized in that: The following steps are involved: S1. Dissolve the iron salt in a solvent to prepare an iron salt solution, add the carbon-based material, polyvinyl pyrrolidone, sodium acetate, and an aminating agent, and stir for 30 min to 120 min at a temperature of 25°C to 45°C and a rotation speed of 400 r / min to 650 r / min to obtain a mixed solution A; before using the carbon-based material, the following treatment is also included: mixing the carbon-based material with water to prepare a carbon-based material dispersion; the ratio of the carbon-based material to the iron salt is 100 mg to 500 mg: 0.002 mol to 0.01 mol; the ratio of the iron salt to the solvent is 3 mmol to 5 mmol: 30 mL to 100 mL; the ratio of the polyvinyl pyrrolidone, sodium acetate, aminating agent, and solvent is 2g to 8 g: 2g to 8 g: 2g to 8 g: 30 mL to 100 mL; the average molecular weight of the polyvinyl pyrrolidone is 40000-130000; the solvent is polyethylene glycol; the degree of polymerization of the polyethylene glycol is 300-1000; the amination agent is urea; S2, subjecting the mixed solution A to a hydrothermal reaction to obtain an aminated magnetic microsphere-carbon-based composite material; the temperature of the hydrothermal reaction is 180° C.; the time of the hydrothermal reaction is 10 h; S3, mixing the aminated magnetic microsphere-carbon-based composite material, LDH precursor, urea and water, stirring to obtain a mixed solution B; the LDH precursor is a soluble divalent metal salt and a soluble trivalent metal salt for preparing layered double hydroxide; S4. Performing a hydrothermal reaction on the mixed solution B to obtain an aminated magnetic microsphere-carbon-based-layered double hydroxide composite material.
2. The preparation method according to claim 1, characterized in that In step S3, the ratio of the aminated magnetic microsphere-carbon-based composite material to the LDH precursor is 100 mg to 500 mg: 0.001 mol to 0.005 mol; the molar ratio of the soluble divalent metal salt to the soluble trivalent metal salt in the LDH precursor is 1:1; and the mass ratio of the aminated magnetic microsphere-carbon-based composite material to urea is 0.1 to 0.6: 1 to 8.
3. The preparation method according to claim 2, characterized in that In step S1, the ratio of the carbon-based material to the iron salt is 250 mg to 500 mg: 0.005 mol to 0.01 mol; In step S3, the ratio of the aminated magnetic microsphere-carbon-based composite material to the LDH precursor is 200 mg to 300 mg: 0.002 mol to 0.003 mol; the mass ratio of the aminated magnetic microsphere-carbon-based composite material to urea is 0.2 to 0.4: 3 to 5.
4. The preparation method according to claim 3, characterized in that The carbon-based material is at least one of carbon nanotubes, graphene, activated carbon, biochar, and carbon cloth; the mass concentration of the carbon-based material in the carbon-based material dispersion is 5% (w / v) to 10% (w / v); the carbon nanotubes are further treated before use: the carbon nanotubes are mixed with concentrated nitric acid, stirred at 95°C to 110°C for 3 h to 6 h, cooled to room temperature, filtered, washed to neutrality, centrifuged at a speed of 5000 r / min to 10000 r / min for 5 min to 10 min, and freeze-dried to obtain acidified carbon nanotubes; The iron salt is at least one of FeCl2, FeCl3, FeSO4, Fe2(SO4)3, Fe(NO3)2, Fe(NO3)3 and (NH4)2Fe(SO4)2·6H2O; The divalent metal cations in the soluble divalent metal salt are one or two of Co, Ni, Cu, Zn, Mg, Fe, and Mn; the trivalent metal cations in the soluble trivalent metal salt are one or two of Al, Ni, Fe, Cr, and In; the acid radical ions in the soluble divalent metal salt and the soluble trivalent metal salt are Cl - 、SO4 2- 、NO3 - One or both of the following.
5. The preparation method according to claim 4, characterized in that: The carbon-based material is at least one of carbon nanotubes and activated carbon; The iron salt is at least one of Fe2(SO4)3 and (NH4)2Fe(SO4)2·6H2O; The molecular weight of the polyvinyl pyrrolidone is 40,000 to 58,000; The degree of polymerization of the polyethylene glycol is 300 to 600; The soluble divalent metal salt is one or two of Co(NO3)2, Ni(NO3)2, and MgSO4; the soluble trivalent metal salt is one or two of NH4Al (SO4)2 and Al2(SO4)3.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In step S2, after the hydrothermal reaction is completed, the following treatment is further included: the product obtained after the hydrothermal reaction is centrifuged at a speed of 6000 r / min to 10000 r / min for 5 min to 10 min, and the product obtained after the centrifugation is washed with ethanol solution and deionized water to obtain an aminated magnetic microsphere-carbon-based composite material; In step S3, the preparation process of the mixed solution B is as follows: adding the aminated magnetic microsphere-carbon-based composite material to deionized water, stirring for 30 min to 120 min at a temperature of 25° C. to 45° C. and a rotation speed of 400 r / min to 650 r / min to prepare an aminated magnetic microsphere-carbon-based composite material dispersion, adding an LDH precursor and an alkaline substance, stirring, and obtaining a mixed solution B; In step S4, the temperature of the hydrothermal reaction is 100°C to 180°C; the time of the hydrothermal reaction is 6 h to 36 h; after the hydrothermal reaction is completed, the following treatment is also included: the product obtained after the hydrothermal reaction is centrifuged at a speed of 5000 r / min to 10000 r / min for 5 min to 10 min, the product obtained after centrifugation is washed with ethanol solution and deionized water, and freeze-dried to obtain an aminated magnetic microsphere-carbon-layered double hydroxide composite material.
7. The preparation method according to claim 6, characterized in that In step S1, the stirring is performed at a temperature of 25°C to 35°C; the stirring speed is 550 r / min to 650 r / min; and the stirring time is 60 min to 90 min; In step S2, the centrifugal speed is 8000 r / min to 10000 r / min; the centrifugal time is 8 min to 10 min; In step S3, the stirring is performed at a temperature of 30°C to 35°C; the stirring speed is 550 r / min to 650 r / min; and the stirring time is 60 min to 90 min; In step S4, the temperature of the hydrothermal reaction is 120° C. to 160° C.; the time of the hydrothermal reaction is 12 h to 36 h.
8. An aminated magnetic microsphere-carbon-based-layered double hydroxide composite material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: It comprises a carbon-based material, the surface of which is loaded with magnetic microspheres to form an aminated magnetic microsphere-carbon-based composite material; the surface of the aminated magnetic microsphere-carbon-based composite material is loaded with layered double hydroxide; the carbon-based material is at least one of carbon nanotubes, graphene, activated carbon, biochar, and carbon cloth; the carbon nanotubes are multi-walled carbon nanotubes, presenting a multi-layer tubular structure with a diameter of 8 nm to 12 nm; the activated carbon and biochar are in powder form with a particle size greater than 200 meshes; the magnetic microspheres are in a spherical structure or a spherical disc structure with a diameter of 10 nm to 100 nm.
9. Use of the aminated magnetic microsphere-carbon-layered double hydroxide composite material as claimed in claim 8 in treating heavy metal wastewater, characterized in that: The application comprises the following steps: mixing the aminated magnetic microsphere-carbon-based-layered double hydroxide composite material with heavy metal wastewater, stirring, and completing the treatment of heavy metals in the wastewater; the mass volume ratio of the aminated magnetic microsphere-carbon-based-layered double hydroxide composite material to the heavy metal wastewater is 1 mg to 5 mg: 5 mL to 10 mL; the heavy metal ion in the heavy metal wastewater is Cd 2+ , Pb 2+ , Cu 2+ 、Zn 2+ 、As 3+ Cr 3+ at least one of the following; the initial concentration of heavy metal ions in the heavy metal wastewater is 10 mg / L to 100 mg / L; the pH value of the heavy metal wastewater is 6 to 8; the stirring temperature is 25°C to 45°C; the stirring speed is 160 rpm to 220 rpm; and the time is 12 h to 24 h.
Citation Information
Patent Citations
Method for preparing carbon nanotube (CNT) / layered double-metal hydroxide (LDH) compound
CN102350279A
Composite material and preparation and application thereof to adsorption and removal of chromium in water body
CN108031440A